Exploiting Surface Plasmon with Dielectric Coating in Copper Wires Waveguide for the Propagation of Terahertz Waves - Arslan Ahmed Sohoo, Arslan Ahmed Sohoo; Fauziahanim Che Seman, Fauziahanim Che Seman; Ahmed Jamal Abdullah Al-Gburi, Ahmed Jamal Abdullah Al-Gburi; Hamza Ahmad, Hamza Ahmad; Yee See Khee, Yee See Khee; Nurul Syafeeqa Binti Ishak, Nurul Syafeeqa Binti Ishak; Thamer A. H. Alghamdi, Thamer A. H. Alghamdi; Moath Alathbah, Moath Alathbah (Mdpi, 2023)
Recently, metallic wires have gained popularity for utilization as waveguides in propagating sub-THz and THz waves through surface plasmonic polaritons (SPPs). Single and double metallic wire waveguides have demonstrated the ability to propagate these high frequencies with minimal loss and nearly zero dispersion. However, wires typically installed commercially are often coated with dielectric material. Therefore, this paper investigated the effects of using two and four metallic copper wires, both with and without dielectric coating. The impact of various gap distances on different propagation characteristics was also analyzed. Computer Simulation Technology (CST) Microwave Studio was employed in this study for electromagnetic simulations of both uncoated and coated configurations of two and four wires. The introduction of a dielectric coating led to an enhancement in reducing conductor losses and improving energy confinement, with the goal of enhancing the overall efficiency of waveguide signal propagation.